Programa de educación financiera para los estudiantes de Bachillerato de la Unidad Educativa Fiscomisional la Dolorosa - Villavicencio Villavicencio, Angie Romina (2022)
This research study refers to financial education applied to high school students of “La Dolorosa”. This study aimed to teach financial knowledge and develop the students’ financial skills so they function in the financial field efficiently. The methodology of this study comprises a quantitative approach for the data collected and an inductive and deductive method. A survey was applied to collect the data and determine the students’ level of financial knowledge. It was evidenced that they were at level 3 in regards to financial education, which reflects a medium level according to the standards based on the PISA model of the Organization for Economic Co-operation and Development (OECD). This diagnosis facilitated the design of a financial education program, which was structured in 5 parts and was implemented through virtual training. Then, a test was applied to evaluate the students’ improvement. It was determined that the students improved to level 5 of financial education, which is the highest level of the PISA model. Thus, it was demonstrated that the application of the program helped the students improve their financial knowledge and skills for their professional and economic development in the future.